Nasopharyngeal Microbiota in Children with Chronic Adenoiditis - F. S. Ikramova (Journal of Science in Medicine and Life, 2025)
The study was carried out in the LOR-Department and polyclinic of the Bukhara regional children's Multidisciplinary Medical Center and in the clinic "BUKHARA LOR MED CENTRE". During the research, a bacteriological examination was carried out, in which all patients were smeared from the burunhalgum. The study examined 154 patient children between the ages of 3 and 18 who were diagnosed with adenoiditis. Among them, boys made up 67.5% and girls made up 32.5%.